O planejamento como fator determinante da boa administração pública - Venâncio, Denilson Marcondes (2010)
This essay is composed of the concerns raised by the practices and theories that have originated in the administrative sector. As the years have passed since these events, we have come to realize that the biggest damages made by the Public Powers were either from imperfect planning or the lack of planning. We start with the text of the Federal Constitution of 1988, which does not systematize the state s planning, but provides many devices to do so. Article No. 174, for example, rules that planning is crucial to the Public Power. We approach every constitutional issue which deals with that matter: thereafter we move onto constitutional legislation and then to the administrative regulations, attempting to demonstrate the remarkable presence of the matter in Positive Law. In the end, we enter the core of the work, taking care of administrative planning as a secondary activity starting with the administrative function and the Juridical obligation of planning and so on, trying to construct the foundations of theoretical administrative planning as a procedure which has been split in three stages: purposes, diagnosis and the action programming. During both doctrinaire and jurisprudential research, we did not find either texts nor judicial decisions or even administrative ones that specifically delved into administrative planning, even though, in a general way, everybody says the latter is both indispensable and inherent to the performance of the administrative function. Nobody seems to conceptualize it but seems to keep it abstract. We have written this essay using the works of several authors and using the judicial sentences handed down which deal with both the planning of the economic and social development, as well as regional and national, budgetary, urban ones, plus the texts both on the educational and entrepreneurial plannings, that were transported to the Judiciary. All of the aforementioned data were, afterwords, collated with both the doctrine and the jurisprudence of the Administrative Law, in line with the classification of the administrative acts. In the execution of administrative functions, no plan, no project or program is made by an isolated act, but by various preparatory or instrumental acts in which some acts have as a scope other acts which are coordinately executed that are bound for purposeful goals. Each and every administrative act has planning behind it. We sought to highlight that planning active services requires structure. Without planning, both the waste and misuse of public funds occur. Planning is an activity which must count on the popular participation of the Democratic State of Law, and constitutes self-control in the exercise of the administrative function. Plans, projects and programs may also be controlled, either internally or externally. We came to the conclusion that Administrative Planning requires a deepening in study and research, as well as the elaboration of a legal instrument looking on its proceedings as a general theory for all administrative acts. In conclusion, this essay expresses a matter which is touched upon by the Law, doctrine and jurisprudence, with an expectation of attracting attention to Administrative Planning as a means of bettering the execution of the administrative function which is coordinated with definite purposes